Strategies to Overcome Antigen Heterogeneity in CAR-T Cell Therapy - Bohan Zhang; Jiawen Wu; Hua Jiang; Min Zhou (Cells, 2025)
Chimeric antigen receptor (CAR) gene-modified T-cell therapy has achieved significant success in the treatment of hematological malignancies. However, this therapy has not yet made breakthroughs in the treatment of solid tumors and still faces issues of resistance and relapse in hematological cancers. A major reason for these problems is the antigenic heterogeneity of tumor tissues. This review outlines the antigenic heterogeneity encountered in CAR-T cell therapy and the corresponding strategies to address it. These strategies include using combination therapy to increase the abundance of target antigens, optimizing the structure of CARs to enhance sensitivity to low-density antigens, developing multi-targeted CAR-T cells, and reprogramming the TME to activate endogenous immunity. These approaches offer new directions for overcoming tumor antigenic heterogeneity in CAR-T cell therapy.